2024
DOI: 10.3390/bs14030214
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Antecedents of Novice STEM Teachers’ Job Satisfaction: The Roles of Personality Traits, Perceived Social Support, and Work Engagement

Zhaochun Wang,
Haozhe Jiang,
Wu Jin
et al.

Abstract: It is reported that teachers’ satisfaction levels are lower and stress levels are higher than other professional groups in many countries. This is especially true for science, technology, engineering, and mathematics (STEM) teachers. Considering job satisfaction has a direct impact on turnover intention, low satisfaction levels have led to high turnover rates and thus exacerbated the shortages of STEM teachers. Hence, there is an urgent need to explore the antecedents of novice STEM teachers’ job satisfaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…In relation to job satisfaction, neuroticism is found to be negatively associated with job satisfaction (Maricutoiu et al, 2023;Van Aarde et al, 2017). In Wang et al (2024) meta-analysis, neuroticism is most strongly correlated with job satisfaction, but in a negative manner. Maricutoiu et al, (2023) in another meta-analysis found that emotional stability-the reverse of neuroticism-is also strongly associated with job satisfaction.…”
Section: Findings and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In relation to job satisfaction, neuroticism is found to be negatively associated with job satisfaction (Maricutoiu et al, 2023;Van Aarde et al, 2017). In Wang et al (2024) meta-analysis, neuroticism is most strongly correlated with job satisfaction, but in a negative manner. Maricutoiu et al, (2023) in another meta-analysis found that emotional stability-the reverse of neuroticism-is also strongly associated with job satisfaction.…”
Section: Findings and Discussionmentioning
confidence: 91%
“…The relationship between neuroticism and job satisfaction is found to be negative (Mamić et al, 2024;Wu et al, 2024). In Wang et al, (2024) meta-analysis, neuroticism has the most negative correlation with job satisfaction. In another meta-analysis, Maricutoiu et al (2023) discovered that emotional stability, the opposite of neuroticism, is similarly highly associated with job satisfaction.…”
Section: Introductionmentioning
confidence: 92%
“…Regression analyses also showed that greater job satisfaction was associated with better mental health and well-being for both women and men, although its relevance depended on the type of mental health indicator used and on gender. Because previous research has shown that job satisfaction is associated with self-esteem and social support [2,18,20,56], to determine whether the effects of job satisfaction on mental symptoms, psychological well-being, and life satisfaction persisted beyond the effects of self-esteem and social support, both variables were included in the regression equation (in Model 3), whereas only job satisfaction was included in Model 2. Although the magnitude of the effect decreased considerably after self-esteem and social support were included in the regression, job satisfaction remained a statistically significant predictor in all regression analyses.…”
Section: Discussionmentioning
confidence: 99%